2011
DOI: 10.18806/tesl.v28i0.1081
|View full text |Cite
|
Sign up to set email alerts
|

“But My Students All Speak English”: Ethical Research Issues of Aboriginal English

Abstract: In this article I explore ethical issues in relation to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The point here is not to make a grand claim of societal injustice, but rather to isolate a problem. There is significant evidence many Indigenous children in Canada are speakers of a non-standard English dialect (Ball and Bernhardt 2008;Battisti, Friesen and Krauth 2014;Eriks-Brophy 2014;Heit and Blair 1993;Kay-Raining Bird 2014;Wiltse 2011). Further, language variation scholars broadly agree that children who speak nonstandard dialects are at an educational disadvantage in schools (E.g.…”
Section: What Is a Nonstandard Dialect And Why Might It Matter?mentioning
confidence: 99%
“…The point here is not to make a grand claim of societal injustice, but rather to isolate a problem. There is significant evidence many Indigenous children in Canada are speakers of a non-standard English dialect (Ball and Bernhardt 2008;Battisti, Friesen and Krauth 2014;Eriks-Brophy 2014;Heit and Blair 1993;Kay-Raining Bird 2014;Wiltse 2011). Further, language variation scholars broadly agree that children who speak nonstandard dialects are at an educational disadvantage in schools (E.g.…”
Section: What Is a Nonstandard Dialect And Why Might It Matter?mentioning
confidence: 99%
“…Kim and Duff 2012;Victoria 2011;Wiltse 2011). Indeed, the existing research method literature generates only a few language education studies in this area (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aboriginal Education has surfaced into the mainstream by interpreting the exact responsibility and reason of education for Aboriginal children, and specifically, on-reserve First Nations learners and was pertinently described through an ethical lens by Wiltse (2011). When studying in the field of Aboriginal Education, Wiltse (2011) suggested in this research piece that linguistics play a major role in student development and that educators must be cognizant of the specific dialect of Aboriginal learners. This article was written in the mode of a retrospective inquiry and related the connection to how Aboriginal children have lost their first language, yet the influence still remains in their style and way of speaking.…”
Section: Direction For Improvement While There Is Much To Be Concernmentioning
confidence: 99%
“…It was suggested that the English used in Aboriginal communities, is in fact a language in and of itself. Wiltse (2011) recognized that there was a bias toward the linguistics of Aboriginal groups because their style of speech is not as fluid and quick paced as the dominant society. The data shared in this article revealed that due to the linguistic traits of Aboriginal speakers, educators must instruct with the pedagogical ideology that Aboriginal dialect do not reflect any deficiency in language acquisition, nor is it a less acceptable method of speaking.…”
Section: Direction For Improvement While There Is Much To Be Concernmentioning
confidence: 99%
See 1 more Smart Citation